PENGARUH PENAMBAHAN AIR REBUSAN BUAH PARE (MOMORDICA CHARANTIA L) DENGAN PERSENTASE BERBEDA TERHADAP SIFAT KIMIA DAN FISIK MIE BASAH - Cahyandari, Maylani Alfi; Rohajatien, Ummi; Wahyuni, Wiwik (Journal of Food Technology and Agroindustry, 2023)
Wet noodles with the addition of boiled water for bitter melon are made from high protein flour, salt, eggs, and boiled water for bitter melon. The purpose of this study was to determine the effect of adding boiled water to bitter melon with different percentages on chemical properties (antioxidant capacity, total flavonoids, and water content) and physical properties (color and elongation). This study used a completely randomized design experimental method with three treatments, namely the addition of boiled water from bitter melon fruit by 60%, 75%, and 90%, and carried out two replications, followed by the One Way ANOVA data test and the Duncan Multiple Test Range (DMRT) follow-up test.). The results showed that the addition of boiled water pare gave a significant effect on the chemical properties (antioxidant capacity, total flavonoids, and water content) and physical properties (color and elongation) of wet noodles with the addition of boiled water from bitter melon.